CLEAVAGE OF ESTERS AND ETHERS WITH SILICA CHLORIDE (Journal of Sciences, Islamic Republic of Iran)
Silica chloride converted benzyl or tert-butyl esters to the corresponding acid chlorides and alkyl chlorides. It also converted benzyl or tert-butyl phenyl ethers to the corresponding allcyl chlorides and phenol